1994
DOI: 10.1073/pnas.91.23.10952
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gamma-aminobutyrate type A receptor subunit mRNAs, translation product expression, and receptor function during neuronal maturation in vitro.

Abstract: The amounts of mRNAs encoding al, a'6, 132, 133, y2, and 8 subunits of y-aminobutyrate type A (GABAA) receptors and the gold immunolabeling density of their translation products were monitored during the growth of neonatal rat granule cells in primary culture. We investigated possible correlations (i) between temporal changes in mRNA content and expression density of their respective translation products and (ii) between the quantitative changes of receptor subunit expression, the GABA EC5. for Cl-channel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 37 publications
7
27
0
Order By: Relevance
“…These results indicate that the apparent affinity of the receptor for GABA increase as granule cells become more matured. Our data are in accord with those reported previously using the cerebellar granule cells (Zheng et al, 1994).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…These results indicate that the apparent affinity of the receptor for GABA increase as granule cells become more matured. Our data are in accord with those reported previously using the cerebellar granule cells (Zheng et al, 1994).…”
Section: Resultssupporting
confidence: 82%
“…2). These findings might be related to an increase in the amount of GABA A receptors containing the ␣6 subunit during granule cell maturation in vitro (Zheng et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the present study has not evaluated whether the fluctuations in ␣ 1 subunit mRNA expression observed here during pregnancy are translated into ␣ 1 subunit protein, previous studies have indicated a positive correlation between ␣ 1 subunit mRNA expression and ␣ 1 subunit protein in vitro (Zheng et al, 1994) and in vivo (Huntsman et al, 1994). It is not unreasonable, therefore, to suggest that the 30 -80% variations in mRNA expression observed here may result in changes in functional subunit protein.…”
Section: Gaba a Receptor Changes Within The Adult Brainmentioning
confidence: 51%
“…with development in vivo and in vitro (Laurie et al 1992;Zheng et al 1993;Mathews et al 1994;Zheng et al 1995). The distinct subunit expression of GABAA receptors in the cerebellum possibly results in the observed heterogeneity of receptor function and pharmacological modulation (Puia et al 1994;Tia et al 1996a;Zhu et al 1996;Mellor & Randall, 1997).…”
mentioning
confidence: 99%